America's world role, Bill Clinton's first year in office, Complete statistics for all major sports (New Jersey, 1993)
The book is the one source for the most up-to-date accurate, reliable, and complete information on U.S. and world affairs. It is composed of nearly 1,000 fact-filled pages, 16 pages of updated maps and flags, 16 pages of color photos
Keywords: almanacs, american